Morphology, membrane nanostructure and stiffness for quality assessment of packed red blood cells - E. Kozlova (Nature Portfolio, 2017)
Abstract Transfusion of packed red blood cells (PRBC) to patients in critical states is often accompanied by post-transfusion complications. This may be related with disturbance of properties of PRBC and their membranes during long-term storage in the hemopreservative solution. The purpose of our work is the study of transformation of morphology, membranes stiffness and nanostructure for assessment of PRBC quality, in vitro. By atomic force microscopy we studied the transformation of cell morphology, the appearance of topological nanodefects of membranes and by atomic force spectroscopy studied the change of membrane stiffness during 40 days of storage of PRBC. It was shown that there is a transition period (20–26 days), in which we observed an increase in the Young’s modulus of the membranes 1.6–2 times and transition of cells into irreversible forms. This process was preceded by the appearance of topological nanodefects of membranes. These parameters can be used for quality assessment of PRBC and for improvement of transfusion rules.